Glucose uptake mechanism of muscle cells and adipocytes stimulated by Scoparia dulcis linn extract - Beh, Joo Ee (2011)
Diabetes mellitus is a metabolism disease which is mainly caused by glucose uptake disorder and decrease of body peripheral cells insulin sensitivity. The aim of the study is to investigate the effect of Scoparia dulcis Linn extracts on glucose uptake mechanism of L6 myotubes and 3T3-F442a adipocytes. In this study, the major problems that need to clarify are cytotoxicity of herbal extracts, complexity of the extracts and cellular protein fractionation. Cytotoxicity studies showed that the water extract of S. dulcis L. leaves showed less toxicity effect on L6 myotubes and 3T3-F442a adipocytes compared with other extracts, which were from petroleum ether, ether acetate and ethanol. Among the extracts, the leaves water extract showed the maximum cell viability from the Trypan blue exclusion test, the highest inhibitory concentration 50 (IC50) from the MTT assay and the lowest tail moment from the Comet assay. The 2-deoxy-D-[3H] glucose uptake assay showed that the leaf water extract significantly enhanced glucose uptake activity on L6 myotubes and 3T3-F442a adipocytes. The result confirmed that the maximum glucose uptake activity due to direct stimulation of TLCseparated fraction 7 (SDF7) of the crude extract on these cells. Four active compounds were successfully identified from SDF7 fraction using C18 reverse phase of HPLC, Mass Spectrometry and NMR assessments. Further studies were carried out to investigate the stimulation effects of glucose uptake mechanism by SDF7 on L6 myotubes and 3T3-F442a adipocytes separately using immunoblotting assay. This study emphasized the allocation and expression of the important downstream effectors of insulin signaling pathway concomitant with the plasma membrane Glut 4 translocation in the SDF7-treated L6 myotubes and 3T3-F442a adipocytes. So, these peripheral cells were divided into four cellular fractions which are plasma membrane fraction, cytosolic fraction, high density fraction and low density fraction using an ltracentrifugation with the different methods approach. For L6 myotubes, the results showed that SDF7 was able to stimulate the expression of IRS-1, PI 3-KINASE, PKB/Akt 2 and TC 10 on the plasma membrane fraction of these cells and triggered the translocation of Glut 4 from the intracellular pool to the plasma membrane of L6 myotubes through an immunoblotting study. Furthermore, the expression of Glut 4 protein on the L6 myotubes plasma membrane was confirmed by an immunofluorescence assay. Glycogen was accumulated in L6 myotubes after being stimulated by of SDF7 as demonstrated by the DNS colorimetric assay and PAS staining assay. An immunoblotting assay demonstrated that the translocation of Glut 4 was accompanied by the expressions of IRS-1, PI 3-Kinase, PKC and TC 10 that traffick from the intracellular pool to 3T3-F442a adipocytes’ plasma membrane when treated with SDF7. Further study was performed to evaluate the amount of Glut 4 on plasma membrane by using an immunofluorescence quantification assay. The results showed that there were a significant increased of Glut 4 on SDF7-treated 3T3-F442a adipocytes membrane in time-dependent and concentration-dependent mode. In addition, the level of adiponectin was increased whereas the level of leptin and TNF-α were decreased on 3T3-F442a adipocytes in response to the SDF7 treatment as evaluated by an ELISA assay. Adiponectin and PPAR-γ mRNA level were being significantly up-regulated in the SDF7-treated 3T3-F442a adipocytes using the Quantigen 2.0 mRNA assay. As the conclusion, Scoparia dulcis Linn has a potential to be categorized as a hypoglycemic medicinal plant based on its good glucose transport activity and Glut 4 translocation on muscle cells and adipocytes.